Sperm Collection and Processing Methods : a Practical Guide. - Jeyendran, Rajasingam S. (Cambridge University Press, 2003)
This practical guide to sperm collection and processing methods demonstrates how successful these procedures are to overcome even severe infertility. This compilation, prepared by an interdisciplinary team of experts, provides clinical and laboratory professionals in reproductive medicine with a comprehensive overview and a useful source of reference. Difficulties with sperm procurement can involve biological deficiencies with sperm creation, delivery, or both. The various procedures described in this text are all designed for one purpose: acquisition of as many viable sperm as possible, given initial patient conditions. Once sperm are collected, a myriad of processing methods are then available to optimize their fertilization potential. Recent advances have made fertility conditions once deemed hopeless a thing of the past. Most sterility cases are now either treatable or entirely circumvented through various clinical and laboratory techniques described in this volume, including surgical correction, hormone treatment, and various sperm enhancement technologies.